Penggunaan Konteks Budaya Ramayana Ballet Prambanan Untuk Soal Literasi Matematika Bagi Siswa SMP - Gunawan, Monica Tiara; Julie, Hongki; Ruditho, M. Andy (Pattimura Proceeding, 2024)
The purpose of this research is to develop and classify mathematical literacy questions using the context of Ramayana Ballet Prambanan Ballet for junior high school students. The type of research used is design research. The data collection methods used were observation, test, and interview. The instrument validation process used by researchers is expert validation and the technique used to test data validity is triangulation technique. The data analysis process used was reducing data, presenting data, and drawing conclusions. The results obtained were from the context of the Ramayana Ballet Prambanan Ballet could be made eight questions in the domain of numbers, data and probability analysis, algebra, measurement, and geometry for cognitive levels (1) knowing with a counting indicator, (2) applying with interpreting, applying/executing indicators, and (3) reasoning with a making justification indicator.